2011
DOI: 10.5488/cmp.14.23603
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in the Mitsui model

Abstract: In this paper, phase transitions in the Mitsui model without longitudinal field but with a transverse one are investigated in the mean field approximation. The one-to-one correspondence has been established between this model and the two-sublattice Ising-type model with longitudinal and transverse fields. Phase diagrams and diagrams of existence of the ferroelectric phase are constructed. In the case Ω = 0 (Ω is the transverse field), a simple analytical expression for the tricritical temperature and the condi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…The phase diagram of the conventional (undeformable) Mitsui model in the (ā,b) plane [36][37][38] shows the regions with different numbers and types of the phase transitions; its topology is not changed by inclusion of the shear strain ε 4 . It has been found that only in a very narrow region of the (ā,b) plane, the system undergoes two second order phase transitions with the intermediate ferroelectric phase.…”
Section: Numerical Calculations 41 Fitting Proceduresmentioning
confidence: 99%
“…The phase diagram of the conventional (undeformable) Mitsui model in the (ā,b) plane [36][37][38] shows the regions with different numbers and types of the phase transitions; its topology is not changed by inclusion of the shear strain ε 4 . It has been found that only in a very narrow region of the (ā,b) plane, the system undergoes two second order phase transitions with the intermediate ferroelectric phase.…”
Section: Numerical Calculations 41 Fitting Proceduresmentioning
confidence: 99%
“…Пiзнiше фазовi дiаграми для моделi Мiцуї докладнiше були вивченi в роботах [19,20]. Однак лише в працi [21] побудовано повну фазову дiаграму моделi Мiцуї й вивчено її змiни пiд впливом тунелювання.…”
unclassified